1996
DOI: 10.1111/j.1439-0264.1996.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Zur Morphologie der Zungenrandpapillen neugeborener Ferkel 1

Abstract: The morphology of the marginal lingual papillae in eight newborn pigs aged 1-5 days was examined at the light-microscopical level, as well as, for the first time, using electron transmission and scanning methods. The papillae marginales are arranged tuft-like or rosetted with chief and accessory papillae, the individual papillae varying considerably in shape. Leaf-, tongue- or fingerlike and conical shapes predominate. The stratified squamous epithelium is either keratinized, resembling the epidermal different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…This study has identified marginal papillae, which have also been seen in various other species including human, cat, dog, pig, whale, and dolphin (4,5,6,16). The results were similar to what the literature reports.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study has identified marginal papillae, which have also been seen in various other species including human, cat, dog, pig, whale, and dolphin (4,5,6,16). The results were similar to what the literature reports.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the marginal papillae normally seen on the lateral edges of the tip of the tongue in the fetal and perinatal periods of human, cat, dog, pig, dolphin, and certain whale species, have been documented to disappear in the postnatal period (4)(5)(6)(7). Even though light and scanning electron microscopic (SEM) observations have been documented on the lingual papillae of the mature domestic pig, domestic pig fetus, and mature wild pig (2,3,8), knowledge of the development of the lingual papillae in the wild pig fetus is limited.…”
Section: Introductionmentioning
confidence: 99%
“…). We hypothesize that the marginal lingual papillae is an adaptation for latching on to the mother's nipple during suckling and the same could be true for the cleft tongue In many mammals (Yamasaki et al, ; Yamasaki and Takahashi, ; Evans, ; Schneider et al, ; Ateş et al, ), including whales (Kastelein and Dubbeldam, ; Shindo et al, ; Ferrando et al, ), the marginal lingual papillae are well developed in juveniles and become reduced or disappear after weaning. The marginal papillae in our specimen are well developed near the apex of the tongue (Fig.…”
Section: Discussionmentioning
confidence: 94%